Target IOP as a measure of glaucoma surgery efficacy - S. Yu. Petrov (Oftalʹmologiâ, 2015)
There are numerous criteria of glaucoma surgery efficacy. Among them, IOP level is of special importance. The development of tolerant and target IOP concepts as well as IOP tolerability issue are reviewed below. Individual normal IOP values and their role in glaucoma surgery evaluation are described. The gradation of glaucoma surgery effect and target IOP level depending on optic nerve damage degree as well as statistical principles of scientific data presentation are discussed. Current controversies forced World Glaucoma Association (WGA) to develop Guidelines on Design & Reporting Glaucoma Trials (2009) which are now recommended for modern studies. The assessment of appropriate IOP reduction is the keystone of this paper. In addition, the results of the above-mentioned studies were analyzed and own recommendations were developed. Two approaches to evaluate glaucoma surgery efficacy are proposed, i.e., by true IOP (P0) and by IOP decrease from baseline (in %). In the last three decades, novel micro-invasive techniques that prolong glaucoma surgery effect were developed. Among them are suture removal (which can be cut or pulled out), laser suture lysis, Nd:YAG laser goniopuncture following non-penetrating surgery, filtering bleb and sub-scleral space needling revision in the early and late postoperative period. These procedures significantly increased hypotensive effect in the late post-op period (up to 96.7 %). Repeated surgery rate and medical therapy need were the primary surgical outcome while complete and partial success rates were the secondary outcome. Baseline IOP was defined as an IOP level on maximum medical therapy pre-operatively. Medical therapy is an important efficacy criterion as well. The number of drugs used (prostaglandin analogues, beta blockers etc.) should be specified. When interpreting surgical outcomes, statistical methods must be considered. The required minimum is Kaplan-Meier survival analysis, scatter diagram, and box diagram.